Evaluación del sistema de compra y venta de maíz y su incidencia en el inventario de la comercializadora Parraga, del periodo 2020 - 2021 - Ballesteros Ballesteros, Andrés Alejandro (2023)
The present research work that was carried out in the Comercializadora Párraga located in the city of Mocache, with the objective of evaluating the incidence of the system of buying and selling Corn in the inventory of the "Comercializadora Párraga" for the Period 2020 - 2021. A qualitative and descriptive methodology was used, research instruments were used, such as the interview to learn about the operational processes and an internal control questionnaire to assess the risks of economic activity, where the different problems and situations of the security system will be delved into. purchase, sale and inventories, in order to include them in an orderly and reliable process based on compliance with legal and accounting regulations. It was concluded that there are high risks, lack of equipment, inventory control system and trained personnel for the process of buying, selling and storing corn, in addition there are problems in the infrastructure and grain management, a process manual is suggested. inventories that will increase the volume of its current operations and develop sustainable growth over time.